Fitoremediasi Menggunakan Kangkung Air (Ipomoea aquatica) untuk Mengurangi Kadar Logam Berat dalam Limbah Cair Pabrik Tahu - Nabila Ma’rufi Ridwan, Radhika; Salma Izzaty, Fatiya; Aprisa, Naomi; Yuliana, Ayu; Nilan Sari Rangkuty, Marlinda; Febriyossa, Adelia (Universitas Cokroaminoto Palopo, 2024)
The tofu industry produces waste in its processing process in the form of solid and liquid waste. One alternative to liquid waste treatment that can be used is the phytoremediation method. Phytoremediation system is a wastewater treatment technique using aquatic plants to help reduce organic substances contained in wastewater. This study aims to determine the effectiveness of water spinach (Ipomoea aquatica) in reducing heavy metal levels in tofu factory wastewater. This research method is experimental research on tofu factory wastewater with the research design used is pretest-posttest with control group. Based on the research obtained water spinach (Ipomoea aquatica) effective in reducing heavy metal levels in tofu liquid waste is evident from the lower TDS levels shown in the treatment using water spinach plants (Ipomoea aquatica) with a concentration of 25% of 1,503 ppm with the length of time required for 6 days.